Pacific Missile Range Draft 613 Congressional Report
A draft of a congressional report examining the disestablishment of the Pacific Missile Range and move it to a government owned-contractor operated basis. Also examines the plans to continue the operation of the Naval Air Station in Point Mugu, California.